2020
DOI: 10.3390/jrfm13100246
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Drones for Tourism in Crises: A Facility Location Analysis Perspective

Abstract: Considering the recent lockdowns and travel bans due to COVID-19, novel tourism strategies are necessary to face the increasing need for innovative products and services and to ensure long-term sustainable growth. This study looks into the potential use of drones in providing online virtual tours of open-space tourist attractions. To do so, a novel mixed-integer linear mathematical model is developed to optimally determine the number and location of required facilities and the number of drones assigned to each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…For instance, European Commission research shows that tour operators now use innovative technologies to develop differentiated tourism products ( Barna and Semak, 2020 ). Through a case study of six historic sites in Rome, Ilkhanizadeh et al (2020) showed that drones might be used to provide live virtual tours of open-space tourist locations, which would be an eco-friendly innovation and solution to the over-tourism problem during pandemics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, European Commission research shows that tour operators now use innovative technologies to develop differentiated tourism products ( Barna and Semak, 2020 ). Through a case study of six historic sites in Rome, Ilkhanizadeh et al (2020) showed that drones might be used to provide live virtual tours of open-space tourist locations, which would be an eco-friendly innovation and solution to the over-tourism problem during pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…The category includes the Internet of Things (IoT) like an electronic key, Radio Frequency Identification (RFID) used by hotels or lodging companies (Costa and Pereira, 2019; Elkhwesky and Elkhwesky, 2022; Farías and Cancino, 2021; Kumar, Maheshwari, Prabhu, Prasanna, Jayalakshmi, Suganya, Malar, & Jothikumar, 2020), high interactivity devices (e.g. voice assistants) (Papagiannidis and Davlembayeva, 2021), robotic room services and contactless hosting (Srivastava, Sengupta, Kumar, Biswas and Ishizaka, 2021), and drones used in providing online virtual tours of open-space tourist attractions (Ilkhanizadeh, Golabi, Hesami and Rjoub, 2020; Mehta and Sharma, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Drones have improved travel experiences through the application of virtual and augmented reality tours (Giuffrida et al , 2021; Hua et al , 2018; Lu et al , 2022). UAVs allowed online virtual tours of tourist attractions during the COVID-19 pandemic lockdowns and border closures (Ilkhanizadeh et al , 2020). The recording of videos and the taking of photographs with drones by tourists during their holidays and sharing these experiences on social networks is also becoming increasingly common (Minucciani and Garnero, 2015).…”
Section: Empirical Analysismentioning
confidence: 99%
“…The mobile servers are predominantly used in emergency location problems. In this case, the servers travel to the location of customers [24,28,45]. In contrast, customers are supposed to visit the servers in the case of immobile servers [53,57].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of lost sales has been rarely considered in the capacitated median problems. While respecting the capacity restrictions, the majority of related studies have assumed that there would be the possibility of covering all the demands using the available resources [28,34,49]. Harris et al [25] developed a bi-objective capacitated inventory-location model to minimize the environmental effects of established facilities and the financial costs simultaneously.…”
Section: Introductionmentioning
confidence: 99%